Multisystemic sarcoidosis with cardiac involvement - S Kopanakis (Journal of the Belgian Society of Radiology, 2014)
Background: A 42-year-old male presented with dyspnea following a syncopal episode a few hours before admission. He had completed his military service 2 months previously. Electrocardiogram showed a complete heart branch block with severe bradycardia measured at 30 bpm. Imaging included chest radiography, CT scan of the chest, heart and abdomen and MRI of the heart.